2020
DOI: 10.3390/antibiotics9110790
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Campylobacter Strains to Selected Natural Products and Frontline Antibiotics

Abstract: Campylobacter species have developed resistance to existing antibiotics. The development of alternative therapies is, therefore, a necessity. This study evaluates the susceptibility of Campylobacter strains to selected natural products (NPs) and frontline antibiotics. Two C. jejuni strains (ATCC® 33560TM and MT947450) and two C. coli strains (ATCC® 33559TM and MT947451) were used. The antimicrobial potential of the NPs, including plant extracts, essential oils, and pure phytochemicals, was evaluated by broth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 82 publications
(108 reference statements)
1
11
0
Order By: Relevance
“…Although the underlying mechanisms were not in the focus of our investigations, direct antipathogenic effects of clove EO are supported by the earlier findings that clove EO is able to kill C. jejuni and other bacteria by the concerted action of membrane destruction and intracellular ROS formation. By the application of 5 g/L clove EO in drinking water we assured that the drug concentrations taken up by infected mice were above the minimum inhibitory concentration (MIC) values which are required to kill C. jejuni in vitro [ 29 ]. This was further confirmed by the MIC of eugenol constituting the major compound of clove EO against the C. jejuni strain 81-176 (i.e., 0.1 g/L; data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the underlying mechanisms were not in the focus of our investigations, direct antipathogenic effects of clove EO are supported by the earlier findings that clove EO is able to kill C. jejuni and other bacteria by the concerted action of membrane destruction and intracellular ROS formation. By the application of 5 g/L clove EO in drinking water we assured that the drug concentrations taken up by infected mice were above the minimum inhibitory concentration (MIC) values which are required to kill C. jejuni in vitro [ 29 ]. This was further confirmed by the MIC of eugenol constituting the major compound of clove EO against the C. jejuni strain 81-176 (i.e., 0.1 g/L; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a treatment option of interest should in parallel dampen innate immune responses with a minimal risk of unwanted side effects. Clove essential oil (EO) appeared as a promising candidate since it has been shown to exert antimicrobial activity against C. jejuni [ 29 ] and other bacterial pathogens mainly by disruption of the outer membrane and by the production of intracellular ROS in the bacteria [ 30 , 31 ]. Furthermore, recent studies revealed that coincubation of C. jejuni with clove EO and its major compound eugenol resulted in compromised pathogenic motility, disturbed spiral-shaped morphology, and diminished virulence factor expression, all of which required for induction of campylobacteriosis [ 11 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two Campylobacter strains used in this study were selected from our previously published research work [8]. For this experiment, preserved strains were revived by inoculating them onto Mueller Hinton Agar as previously described [33].…”
Section: Campylobacter Strains and Culture Conditionsmentioning
confidence: 99%
“…Chicken ceca are colonized by high levels of Campylobacter which may persist in feces that are used as biofertilizers [7]. Human campylobacteriosis is of public health concern due to the increased number of Campylobacter strains that are resistant to both drugs of choice (macrolides and fluoroquinolones) and alternative therapies (aminoglycosides and tetracyclines) [8]. The missense mutation (C257T) in the quinolone resistance-determining region (QRDR) of gyrA has been associated with high-level resistance to quinolones [9].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic-resistant C. jejuni isolates have been observed and reported in recent years (Marotta et al, 2020;Tang et al, 2020;Hull et al, 2021). A recent study reported that some natural products, including plant extracts, essential oils, and pure phytochemicals, are effective against drug-sensitive and drug-resistant Campylobacter strains (Gahamanyi et al, 2020). These natural products can be used alone or in combination to kill C. jejuni.…”
Section: Introductionmentioning
confidence: 99%